Estradiol mediates the interaction of LINC01541 and miR-429 to promote angiogenesis of G1/G2 endometrioid adenocarcinoma in-vitro: A pilot study - Qiao, Dan; Qin, Xiaoduo; Yang, Haiyan; Liu, Xuantong; Liu, Libing; Liu, Sufen; Jia, Zhongzhi (Frontiers in Oncology, 2022)
Background: Endometrioid adenocarcinoma (EAC) is the most common subtype of endometrial cancer (EC) and is an estrogen-related cancer. In this study, we sought to investigate the expressions and mechanism of action of 17β-estradiol (E2) and long noncoding RNA (lncRNA) LINC01541 in G1/G2 EAC samples. Methods: The expressions of ESR2, LINC01541, miR-200s, and VEGFA were evaluated using quantitative real-time polymerase chain reaction (qRT-PCR) in human EAC tissues (n = 8) and normal tissues (n = 8). Bioinformatics analyses and luciferase reporter analyses were performed to verify potential binding sites. qRT-PCR and Western blot analysis were used to identify the regulatory mechanisms of estrogen receptor β (ESR2), LINC01541, and miR-200s in cell biological behavior. Results: E2 was found to promote the expression of VEGFA by changing the expression levels of LINC01541 and miR-429 in EAC. In addition, mutual promotion was established between LINC01541 and miR-429. Conclusion: These findings regarding the E2/LINC01541/miR-429/VEGFA axis illustrate its potential as a target for EAC therapeutic development.